lmmunological alterations in splenectomized patients: Laboratory evaluation at the clinic - Ant´unez da Graça, Carlos; Schuhl, Juan Francisco; Oheninger (h), Carlos; Bergalli, Luis; Torterolo, Edgardo (Cirugía del Uruguay, 1984)
The lncrease In the rate of aerlous lnfectlon found In aplenectomlzed patlenta led authora to stud.y the lm• munologlcal condltlon of two comparable groups of people. The flrst corresponda to adulta splenectoml• zed on account of trauma; the second, actlng as wlt• ness, corresponda to non-splenectomlzed adulta, In good health. The authors recorded thelr atudy of celular and hu• moral lmmunlty and, on the basls of resulta concluded that splenectomlzed patlents show an lmmunologlcal deflclency of statlstlcal slgnlflcance and lndependent of any underlylng pathology.